Supervising Counselors-in-Training Through a Developmental, Narrative Model. Issue 1 (2nd January 2017) - Zeligman, Melissa
ABSTRACT: The developmental narrative model (DNM) to supervision introduces a creative postmodern supervision approach designed to increase counselor-in-training competency through counselor awareness, the use of storying, and a commitment to social advocacy. This collaborative supervision model pulls from narrative therapy and incorporates the developmental needs of counselors-in-training through the integrated developmental model. The purpose of this article is threefold: (a) review the major tenets of DNM supervision, (b) present the supervisors' role within the approach, and (c) identify strengths and limitations of the DNM model in action.